Good enough? The 'wicked' use of testosterone for defining femaleness in women's sport. Issue 4 (23rd March 2021) - Schultz, Jaime
Abstract: Since the 1930s, sports administrators have insisted on various mechanisms to assess 'femaleness' for the purpose of competition in women's sport. Most recently, the criterion has turned to testosterone. Specifically, if a woman naturally produces testosterone that registers in what sport authorities consider an 'unnatural' range, she must suppress that testosterone to compete in women's events. The testosterone threshold will undoubtedly expand to include cis, intersex, and trans sportswomen, despite their respective and significant differences. Taken together, these types of regulations are confusing and contradictory, quite possibly sexist, and most assuredly 'wicked', as Rittel and Webber formulated with regard to 'wicked problems'. A historical analysis of the regulations for 'femaleness' in sport, contextualized with other testosterone-related policies, reveals the impossibility of sex determination, the faulty assertion that testosterone is a 'male hormone', and the prioritization of sporting rights over human rights.